Confronting scale in watershed development in India - Syme, G.J.; Reddy, V.R.; Pavelic, Paul; Croke, B.; Ranjan, R. (Springer, 2012)
The issue of scale is examined in the context of a watershed development policy (WSD) in India. WSD policy goals, by improving the natural resource base, aim to improve the livelihoods of rural communities through increased sustainable production. It has generally been practiced at a micro-level of less than 500 ha, as this was seen to be a scale that would encourage participative management. There has been some concern that this land area may be too small and may lead to less than optimal hydrological, economic and equity outcomes. As a result there has been a move to create guidelines for meso-scale WSD of above 5,000 ha in an endeavour to improve outcomes. A multidisciplinary team was assembled to evaluate the proposed meso-scale approach. In developing an adequate methodology for the evaluation it soon became clear that scale in itself was not the only determinant of success. The effect of geographical scale (or level) on WSD is determined by the variation in other drivers that will influence WSD success such as hydrological conditions, land use and available institutional structures. How this should be interpreted at different levels in the light of interactions between biophysical and socio-economic scales is discussed.